Multiple authorship of the Septuagint Pentateuch : the origin of the Septuagint - Kim, Hayeon, (Supplements to the Textual History of the Bible;, 2020)
"For hundreds of years, disputes on the origin of the Septuagint, a biblical text that was translated from Hebrew into Greek in the third century BCE, and the number of its translators have been ongoing. In Multiple Authorship of the Septuagint Pentateuch, Hayeon Kim provides a clear solution to the unsolved questions, using objective and consistent set of translation-technique criteria, and traditional and computerized tools of analysis. According to the author, the translation of the Septuagint Pentateuch has two facets: homogeneity and heterogeneity. The common socio-religious milieu of the translators is apparent in the similar translation techniques, however, the individual characters of the five translators are also evident in their distinct translation styles"--Provided by publisher.